Dampak Doktrin Pluralisme Agama terhadap Kehidupan Sosial - Mohammad Harir Saifu Yasyak (Universitas Darussalam Gontor, 2017)
The issue of diversity or plurality in religion is quite interesting issue interesting to be analyzed. It is because the phenomenon of religious pluralism has become a real social facts and become a part of modern life. For those who are not familiar, and have no experience in peaceful coexistence, it will cause problems, so it is forcing experts from various disciplines to find a solution in order to respond the problems. In the end, numbers of religious pluralism theories appear. Some of them are Global Theology and Transcendent Unity of Religions. If it is investigated accurately, the final target of both theories is an attempt to legitimize the truth of all religions. In addition, the most troubling is the effort to no longer claiming absolute truth. Thus, the social impact of the doctrine of religious pluralism is quite dangerous to the teachings of the religion that has been going well. For Islam, the presence of religious pluralism can not be accepted because it will negatively affect the pillars of Islamic teaching. The impact also affects social life of Islamic community. Therefore, this paper will try to research negative influence brought by religious pluralism against Islam. The research will be focused on social life matters such as interfaith marriage, praying together, and also theological dialogue between religions.